2022
DOI: 10.1021/acs.jpclett.2c01940
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Polaron and Enormous Light-Induced Fermi-Level Shift at Halide Perovskite Surface

Abstract: Halide perovskites intrinsically contain a large amount of point defects. The interaction of these defects with photocarriers, photons, and lattice distortion remains a complex and unresolved issue. We found that for halide perovskite films with excess halide vacancies, the Fermi level can be shifted by as much as 0.7 eV upon light illumination. These defects can trap photocarriers for hours after the light illumination is turned off. The enormous light-induced Fermi level shift and the prolonged electron trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Recently, a series of phenomena, e.g. the significant shift of Fermi energy levels reaching the value of 700 meV [34], prolonged electron trapping and enhanced defect migration [31], have been proved by experiments in MHPs, all of which could be attributed to the formation of defect-polaron states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a series of phenomena, e.g. the significant shift of Fermi energy levels reaching the value of 700 meV [34], prolonged electron trapping and enhanced defect migration [31], have been proved by experiments in MHPs, all of which could be attributed to the formation of defect-polaron states.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the first-principles calculations predict that holeinjection and ion migration can form deep states and accelerate the nonradiative recombination due to the strong distortion of lattice [30,31]; the strong covalency at certain charge states gives rise to deep trapping levels within the band gap, which could be attributed to to the defect coupling with the distortion lattice field [32]; electrons trapping by the interstitial defects undergo the formation processes of defect-polarons in CH 3 NH 3 PbI 3 [33]. Recently, Alkhalifah et al found that the Fermi level can be shifted in a very large scale upon light illumination in halide perovskite films with excess halide vacancies, in which the formation of defect-photocarrier complex leads to lattice deformation and an energy shift of defect state [34]. They suggested that the whole process can be explained by the polaron formation at a defect site.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Correspondingly, the remaining V I defects induced an upshift of CBM. [40,41] Therefore, a direct correlation was conjectured between the iodine activity and Sn 2+ autoxidation.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Since the SPV signal depends on the Fermi level and the Fermi level change under illumination in the sample, it is influenced by band bending, doping, [49] and stoichiometry in the sample. [50] Figure 1. Schematic overview of the tr-KPFM setup.…”
Section: Surface Photovoltage and Surface Photovoltage Decaymentioning
confidence: 99%